(untitled) (Ustozlar uchun, 2026)
This academic article explores the interconnected dynamics of three fundamental pillars of modern tourism: travel items (material culture), transportation (mobility infrastructure), and holiday activities (experiential consumption). Drawing upon theories from material culture studies, transport geography, and tourist experience literature, this paper argues that these three elements do not operate in isolation but form a synergistic system that dictates the quality, sustainability, and memorability of a holiday. The research synthesizes existing literature to analyze how the choice of luggage and gear reflects tourist identity, how transportation modes shape the spatial and temporal experience of a destination, and how these factors collectively influence the selection and execution of leisure activities. The article concludes that a holistic understanding of this triad is essential for tourism industry stakeholders, policymakers, and travelers